PARANEOPLASTIC VITELLIFORM MACULOPATHY ASSOCIATED WITH METASTATIC MELANOMA. (2018) - Rahimi, Mansour; Navajas, Eduardo V.; Sarraf, David
Abstract : Purpose: To report a case of paraneoplastic vitelliform maculopathy in a patient with metastatic melanoma of unknown primary site. Methods: Case report. Main outcome measures include funduscopic examination, fluorescein angiography, fundus autofluorescence, and spectral domain optical coherence tomography. Results: A 44-year-old man with a known history of metastatic melanoma was referred for ophthalmic evaluation because of bilateral vision loss. Funduscopic examination was remarkable for vitelliform maculopathy that was confirmed with fundus autofluorescence and spectral domain optical coherence tomography. Conclusion: We describe a rare case of paraneoplastic vitelliform maculopathy. There are many etiologies of acquired vitelliform retinal lesions in the retina. Multimodal retinal imaging, including fundus autofluorescence and spectral domain optical coherence tomography, can be best used to identify these lesions. A history of systemic metastatic melanoma should be ruled out in patients with vitelliform maculopathy. Abstract : The authors present a case of vitelliform maculopathy in a patient with vision loss and a history of metastatic melanoma. There are many etiologies of acquired vitelliform retinal lesions, including the rare association of systemic metastatic disease.